TNF-alpha polymorphisms as a potential modifier gene in the cystic fibrosis - Coutinho, Cyntia AAC (e-Century Publishing Corporation, 2014)
Modifier genes, as the TNF-α gene, can modulate the cystic fibrosis (CF) severity. Thus, -238G>A and -308G>A polymorphisms of TNF-α gene were analyzed as modifiers of CF. In this context, the present study enrolled 49 CF patients (diagnosis performed by sweat test and complete CFTR screening). The -238G>A polymorphism analysis was performed by ARMS-PCR, and -308G>A, by PCR-RFLP. In our data, the -238G>A polymorphism was not associated with clinical variability. The AA genotype for -308G>A polymorphism was a risk factor for early gastrointestinal symptoms (OR=5.98, 95%CI=1.06-49.68) and protection for the first Pseudomonas aeruginosa (OR=0.05, 95%CI=0.0003-0.007). For the first P. aeruginosa, GA genotype was a risk factor (OR=10.2, 95%CI=1.86-84.09); for the same genotype, the diagnosis was made in minor time than the AA genotype (p=0.031). Considering the -308G>A polymorphism alleles, the G allele was a risk factor for early pulmonary symptoms (OR=3.81, 95%CI=1.13-12.97) and P. aeruginosa (OR=66.77, 95%CI=15.18-482.7); however, the same allele showed better transcutaneous oxygen saturation (OR=9.24, 95%CI=1.53-206.1). The A allele was a protective factor for early pulmonary symptoms (OR=12.26, 95%CI=0.08-0.89) and P. aeruginosa (OR=12.15, 95%CI=0002-0007), however, the same allele was a risk factor for worst transcutaneous oxygen saturation (OR=7.01, 95%CI=1.14-157.4). As conclusion, the -308G>A polymorphism of the TNF-α gene was associated with the CF severity.